CORD BLOOD ALBUMIN AND BILIRUBIN LEVELS AS PREDICTORS IN NEONATAL HYPERBILIRUBINEMIA - GOWTHAMI SANDHYA DWARAMPUDI,; N. RAMAKRISHNA, (International Journal of Pharma and Bio Sciences, 2015)
Neonatal hyperbilirubinemia resulting in clinical jaundice is a common problem during the first weeks of neonates life. Most common cause of hyperbilirubinemia in neonates is physiological hyperbilirubinemia. Although physiological hyperbilirubinemia is 100% curable;Fallow up and the early treatment has become difficult due to early discharge from the hospital. Physiological hyperbilirubinemia results from immature liver cell having very low uridine diphospho glucuronosyl transferase activity compared to mature hepatocyte, low concentration of Bilirubin binding ligand Albumin, and higher volume of short life erythrocytes in the circulation. Studies strongly argues for the primacy of bilirubin in the etiology of kernicterus. present study: estimation of neonatal cord blood albumin and bilirubin levels and assessing their reliability with the third day neonatal peripheral venous sample bilirubin levels. To assess the reliability of cord blood albumin and bilirubin levels in early prediction of Hyperbilirubinemia in neonates. Present study was conducted on 70 neonates (term & preterm) whose cord blood was estimated for albumin and bilirubin levels by dye binding method and modified dimethylsulfoxide methods respectively. Incidence of Hyperbilirubinemia is confirmed by estimating peripheral venous blood bilirubin levels by DMSO method on day third of the neonate . Frequency of hyperbilirubinemia in neonates in our center at term is 52 % and in pre-tem is 70% 10,11.. Cord blood albumin level of < 2.8 gm/dl has a sensitivity of 74% and specificity of 88%9,13and Cord bilirubin level >2mg/dl has 70% sensitivity and 90%specificity 7, 9, in predicting the risk of neonatal hyperbilirubinemia. Present study supports that Cord blood albumin and bilirubin levels are reliable in predicting development of hyperbilirubinemia. This study also supports gestational age has impact in developing hyperbilirubinemia. By early detection of hyperbilirubinemia treatment option will be simple phototherapy which prevent neonate from having unnecessary transfusions. Recommendations: Hence it is recommended to include estimation of cord blood albumin and bilirubin levels as a routine investigation for the neonates to prevent the dangerous consequences of neonatal hyperbilirubinemia like kernicterus. ABREVATIONs: CSA: Cord serum Albumin, TB: Total bilirubin, UB: Un conjugated bilirubin.